Investor Horizons and Corporate Policies - Derrien, François; Kecskés, Ambrus; Thesmar, David (Journal of Financial and Quantitative Analysis, 2013)
Abstract We study the effect of investor horizons on corporate behavior. We argue that longer investor horizons attenuate the effect of stock mispricing on corporate policies. Consistent with our argument, we find that when a firm is undervalued, greater long-term investor ownership is associated with more investment, more equity financing, and less payouts to shareholders. Our results do not appear to be explained by long-term investor self-selection, monitoring (corporate governance), or concentration (blockholdings). Our results are consistent with a version of market timing in which mispriced firms cater to the tastes of their short-term investors rather than their long-term investors.